Comparative Efficacy of Fish Meal Replacement With Enzymatically Treated Soybean Meal on Growth Performance, Immunity, Oxidative Capacity and Fecal Microbiota in Weaned Pigs - Yang, Ning; Li, Mohan; Huang, Yuetong; Liang, Xiaona; Quan, Zhizhong; Liu, Haiying; Li, Jiantao; Yue, Xiqing (Frontiers in Veterinary Science, 2022)
This study investigated the growth performance, immunity, antioxidant capacity and fecal microbiota of weaned pigs by partially or completely replacing dietary fishmeal with enzymatically treated soybean meal（ESBM）. A total of 144 piglets weaned at 28 d were allotted to 3 dietary treatments (6 replicates per treatment): 4% fish meal diet (FM); 2% fishmeal plus 6% ESBM (ESBM1); and 6% ESBM without fish meal (ESBM2). The body weight, average daily gain and average daily feed intake of piglets in the ESBM2 group were significantly increased compared with those in the FM and ESBM1 groups from 0-28 d, respectively (P<0.05). The diets with enzymatically treated soybean meal in ESBM1 and ESBM2 groups decreased the diarrhea rate (P<0.05). Compared with FM, ESBM1 and ESBM2 decreased 5-hydroxytryptamine (P<0.05). ESBM1 decreased diamine oxidase and Interleukin 6 compared with FM and ESBM2 (P<0.05). ESBM1 decreased serum Interleukin 1β compared with FM at d 14 (P<0.05). The serum Immunoglobulin E , secretory curl associated protein 5 were higher in ESBM1 compared with FM and ESBM2 (P<0.05). ESBM2 increased super oxidase dismutase level and decreased malondialdehyde content compared with FM and ESBM1, the concentration of SOD in ESBM1was higher than that in FM (P<0.05). ESBM1 decreased cortisol and caspase 3 (P<0.05). The concentration of leptin was lower in ESBM2 (P<0.05). ESBM1 had a higher α-diversity than ESBM2 (P<0.05). The microbiota composition was different among three treatments (difference between FM and ESBM1, p=0.005; FM and ESBM2, p=0.009; ESBM1 and ESBM2, p=0.004). ESBM2 tend to increase the abundance of Firmicutes (P=0.070) and decrease Bacteroidetes (P=0.069). ESBM2 decreased the abundance of Parabacteroides and increased SMB53 compared with FM (P<0.05). The spearman correlation analysis revealed that the abundance of Parabacteroides enriched in FM group was negatively correlated with SOD, Megasphaera enriched in ESBM2 group were positively correlated with SOD. The abundance of Lachnospira enriched in ESBM2 group were negatively correlated with serum concentration of D-lactate, DAO, IL-6 and NO. In conclusion, under the conditions of this study, diet with only ESBM demonstrate the beneficial impact on intestinal microbiota developments, antioxidant capacity as well as growth performance for weaned pigs